An unusual cause of abdominal pain - Patil, Gaurav; Iyer, Arun; Vadgaonkar, Amol; Dalal, Ankit; Maydeo, Amit (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Patil G, Iyer A, Vadgaonkar A, Dalal A, Maydeo A. An unusual cause of abdominal pain. Turk J Gastroenterol 2020; 31(7): 547-8.